Class, Culture and Community: A Biographical Study of Social Change in Mining - Seager, Allen (Labour / Le Travail, 1985)
This article reviews the book, "Class, Culture and Community: A Biographical Study of Social Change in Mining," by Bill Williamson.
Keywords: CLASS, Culture & Community: A Biographical Study of Social Change in Mining (Book); Nonfiction; REVIEWS; Social change; WILLIAMSON, Bill; books